Interaction Between a South African Population of Xiphinema index and Different Grapevine Rootstocks - Malan, Antoinette P.; Meyer, A.J. (South African Journal of Enology and Viticulture, 2017)
Thirty-one grapevine rootstocks were used to test for reproduction, root feeding symptoms and transmission of grapevine fanleaf virus by a South African population of Xiphinema index. Grapevine fanleaf virus was transmitted within four months to the roots and systemically spread within six months to the leaves of all the rootstocks tested. No root damage and a low reproduction rate of X. index were found on the rootstocks Harmony, Freedom and 1613 C, all which have V. Longii and Othello in their parentage.